Heroes of Diabetica: Game Pembelajaran Edukasi Diabetes untuk Anak - Ahmad Fathannafi; Rahadian Kurniawan (Universitas Hamzanwadi, 2023)
Learning media is a tool or means used to facilitate the delivery of information, concepts, and skills in the educational process. In the healthcare industry, one prominent application of learning media is through games, especially serious games. Serious games are interactive software designed to provide education in an engaging manner that involves gaming elements. This study aims to analyze the development of a serious game called 'Heroes of Diabetica' to provide diabetes education and deliver interactive and engaging learning to children. The research method employed in this study utilizes the research and development (R&D) approach. The game development process follows the ADDIE Model, involving the stages of analysis, design, development, implementation, and evaluation. Data collection was conducted through game testing and questionnaire responses from 20 participants. The results of the study indicate that 'Heroes of Diabetica,' developed as an RPG game, effectively created a suitable educational tool for children aged 10–15 to deliver basic information about diabetes, including symptoms, definition, causes, types, management, long-term effects, and understanding the importance of the disease. User response results using the USE Questionnaire show that this game provides a better understanding of diabetes, combined with an enjoyable gaming experience for players, and the game can be played without causing difficulties for the players.